Mixed-layer Heat Budget in Western and Eastern Tropical Pacific Ocean during El Niño Event in 2015/2016 - Kusuma, Willy Anta; Nur, Muhammad; Khakim, Mokhamad Yusup Nur; Iskandar, Iskhaq (UI Scholars Hub, 2020)
Temporal variation of mixed-layer heat budget at two contrasting locations, namely, western Pacific (warm water pool) and eastern Pacific (cold tongue) during the extreme El Niño phenomenon in 2015/2016 is evaluated. Oceanic and atmospheric datasets, including sea surface temperature (SST), wind stress, shortwave radiation (SWR), longwave radiation, latent heat flux (LHF), and sensible heat flux are analyzed. A slight warming occurred in the eastern tropical Pacific associated with a positive SST anomaly, which reflected the weakening or reversal of the trade winds. Meanwhile, the western tropical Pacific exhibited a cooling tendency during the development phase of El Niño. Analysis of the mixed-layer heat budget shows that the net heat flux due to SWR and LHF significantly contributes to the warming of the eastern tropical Pacific. The contribution from horizontal advection was extremely small on both sides. The analysis shows that the residual term significantly contributes to cooling (warming) tendency observed in the western (eastern) tropical Pacific. This condition may suggest that residual process due to entrainment and diffusivity played an important role in the evolution of cooling (warming) process in the western (eastern) tropical Pacific.